"Do they really know what we need?"Exploring learners' versus universities' views on open educational resources in Chinese universities. (2021) - Chen, Zhiwei; Liu, Ying; Hou, Huihong
Highlights: The main problem of OER in China comes from the mismatch of supply and demand. 10 universities and 300 individuals in Beijing were studied through surveys. Universities carry out OER mainly based on the conditions and abilities of campuses. The demand for OER by societal learners was mainly based on their own practical needs. The problems of OER can be addressed from the macro, meso and micro level. Abstract: The study investigated open educational resources (OER) from the perspectives of higher education and society. Surveys were distributed to 50 teaching staff in 10 typical universities and 300 learners in Beijing, and interviews were conducted with a subset of 10 university teachers and 10 learners. Findings showed different views and understandings of OER. Specifically, university respondents viewed OER based mainly on its current status and the level of OER provided by their universities. In contrast, learners' demand for OER was based mainly on their own practical needs. Key areas of difference between the two groups were related to the degree, categories, channels, orientation, and content of OER. Problems arising in the OER process should be analyzed and resolved based on human factors, clarifying available university resources and learners' needs.